Edith - Devlin, Martina Josephine (Trinity College Dublin. School of English. Discipline of English, 2021)
This project contains two elements, one creative and the other critical. The creative component is a novel in the voice of Edith Somerville as she attempts to convince herself, and others, that the Somerville and Ross literary firm remains viable after the death of her writing partner, Violet Martin (Martin Ross), and that civil unrest in Ireland can neither undermine her work practices nor diminish her audience. The second strand reflects on Somerville s little-known play, Flurry s Wedding (1921-2), and critically evaluates why the silence surrounding it represents a lacuna in the scholarly appraisal of a writer with canonical status. The critical component rectifies that omission. Flurry s Wedding, based on the Irish R.M. stories, was never staged and critics have mentioned it only in passing without attaching any importance to its existence. Nevertheless, its presence amid Somerville s body of work is significant because it sheds new light on her literary practice. Far from immobilising her, the play s failure preceded a burst of literary application which resulted in Somerville s most noteworthy solo novel, The Big House of Inver (1925). This study will suggest that Flurry s Wedding acted as a statement of Somerville s capacity to recognise the need to adapt, rather than restrict herself to what has proven to be successful. Its existence showcases a writer some thirty years into her literary career with the interest and confidence to continue exploring new genres. It also reflects on her interest in drama, and offers further proof of her lifelong commitment to earning a living as a mark of independence. Together, these two components combine to provide new creative and critical insights into an Irish writer of substance who managed to negotiate a pathway through an increasingly capricious environment.
APPROVED
Keywords: Edith Somerville, Violet Martin, Somerville and Ross, Irish writers, literary partnerships, theatre, Dame Ethel Smyth, George Bernard Shaw, The Irish R.M.